THE EFFECT OF SERVICE QUALITY AND INTEREST RATES ON CREDIT DECISIONS AT PT PEGADAIAN UPC GLUGUR MEDAN - Wirna Sinaga; Nalom Siagian; Lampola Sitorus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
: This research was conducted to evaluate the impact of service quality and interest rates on credit decision-making at PT Pegadaian UPC Glugur Medan. The study utilized a quantitative approach, with data gathered through a questionnaire. The population consisted of customers from Pegadaian UPC Glugur Medan. The sample size was determined using the Slovin formula, leading to a total of 98 respondents. Accidental sampling was the method used for selecting participants. Data analysis was performed using SPSS version 26.0. This study fulfilled both validity and reliability criteria. The data analysis included classical assumption tests and multiple linear regression tests, with the variable X1 (Service Quality) showing a coefficient of 0.375, the variable X2 (Interest Rate) at 0.382, and an R-squared value of 0.701. The findings of this research indicate that both service quality and interest rates exert a simultaneous and individual influence on credit decision-making.